KESEJAHTERAAN MASYARAKAT DAN PERTUMBUHAN EKONOMI DI PERBATASAN JAGOI BABANG KALIMANTAN BARAT MELALUI PEMBERDAYAAN - Sabinus (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
This research was conducted in Jagoi Babang Subdistrict, which has a land boundary with Serikin Sarawak Malaysia, where the current condition of the Border Crossing Post has not been officially opened. This study aims to see the level of welfare of the community at the Jagoi Babang border of West Kalimantan before the opening of the Transboundary Post. from the Central Statistics Agency of Bengkayang Regency with data on findings in different fields, this is because economic activities are only enjoyed by people who have financial capacity and entrepreneurs, while local people who do not have capital do not get complete attention by the government, for example by providing assistance through improvements. human resources so that later when the border is officially opened, the local community can compete optimally. Government interventions are limited to providing social assistance but have not been able to reach the whole Jagoi Babang community, the expected assistance is in the form of entrepreneurship training and assistance with access to capital from the government, the provision of facilities and infrastructure for improving human resources, namely quality schools and the existence of Vocational High Schools that can answering the needs that will come when opening borders and health facilities that can compete with Malaysia and development that includes local wisdom. The methods used are quantitative methods and qualitative methods as complementary methods with data collection techniques in the form of observations and interviews with the Jagoi Babang border community and in the following year further research will be carried out after the opening of the National Border Crossing Post, whether there is an increase in community welfare or the opposite with hope in the future can be the main source in writing a book on the development of the land border area of ​​Indonesia-Malaysia.